Prevalence of COVID-19 Vaccine Hesitancy and Its Associated Factors among Chronic Disease Patients in a Resource Limited Setting in Ethiopia: A Cross-Sectional Study - Eden Abetu Mehari; Tafete Getu Mekonen; Melkamu Tesfahun Adugnaw; Ousman Abubeker Abdela (Hindawi Limited, 2023)
Background. The COVID-19 pandemic disproportionately affects patients with chronic diseases. Thus, chronic disease patients are among the first high-risk population groups to get vaccinated. This might be challenged by vaccine hesitancy as it is one of the top ten global health issues for 2019. Furthermore, vaccination myths and conspiracy theories have been proliferating, and the developing world can readily embrace them, which might cause vaccine hesitancy. However, there is a paucity of evidence regarding chronic illness patient's willingness to be vaccinated. As a result, the aim of this study is to determine the magnitude of vaccine hesitancy and associated factors among chronic disease patients in Ethiopia. Method. An institutional-based cross-sectional study was conducted among adult ambulatory chronic disease patients who were selected using stratified sampling technique from June 1 to August 1, 2021. Data were collected through a face-to-face interviewer-administered questionnaire. Vaccine hesitancy was measured based on a questionnaire which was adapted from the reviewed literature. Bivariable and multivariable logistic regression was used to identify factors, and variables with p<0.05 were considered statistically significant. Result. A total of 422 respondents participated in the survey; the response rate was 99.7%. The mean age of the participants was 45 years ± 16.95 and 228 (54%) of them were male. Almost half of the respondents (49.5%) were hesitant toward the COVID-19 vaccine. Participants who were male (AOR = 1.56, 95% CI: 1.03, 2.35), having good knowledge about the COVID-19 vaccine (AOR = 1.60 95% CI: 1.06, 2.41) and having a comorbidity (AOR = 3.36, 95% CI: 1.73, 6.56), were factors associated with the acceptance of the COVID-19 vaccine. Conclusion. The level of COVID-19 vaccine hesitancy was high. The COVID-19 vaccine's acceptability was influenced by being a man, having knowledge about the vaccine and having comorbidities. Furthermore, the most prevalent reason for refusing to take the vaccination is a fear that it may not be safe. As a result, public awareness campaigns should concentrate on delivering more information about the COVID-19 vaccine's safety and efficacy. Furthermore, it is critical to disseminate accurate information, particularly among women, and to educate people about the vaccine.